2016
DOI: 10.1111/add.13641
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of using the UPPS model of impulsivity rather than the Big Five when assessing the relationship between personality and problem gambling

Abstract: Brunborg et al.'s recent paper [1] focuses on the relevance of personality factors associated with problem gambling (PG) in a study in which personality traits were examined along with subclinical gambling problems in a large-scale epidemiological sample. The study offers new insights into specific personality traits associated with PG, namely high neuroticism and low conscientiousness [1]. If these traits are indeed the most relevant personality dimensions linked to PG, then in our communication we would like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…It has shown adequate psychometric properties (Cronbach's α values ranging from 0.61 to 0.81). Our interest focused on NU, due to its relationship with GD severity and poorer treatment outcomes and emotion dysregulation . The Cronbach's α of the NU subscale in the current sample was 0.81.…”
Section: Methodsmentioning
confidence: 91%
“…It has shown adequate psychometric properties (Cronbach's α values ranging from 0.61 to 0.81). Our interest focused on NU, due to its relationship with GD severity and poorer treatment outcomes and emotion dysregulation . The Cronbach's α of the NU subscale in the current sample was 0.81.…”
Section: Methodsmentioning
confidence: 91%
“…Although the 5‐factor model includes many characteristics that may be linked to sexting, there appears to be conceptual overlap among the 5 factors, such as impulsivity and susceptibility to peer pressure. The UPPS‐P (urgency, premeditation, perseverance, sensation seeking, and positive urgency) was used to represent 4 of the 5 personality factors that were linked to aspects of disinhibition, which has been recommended as an appropriate method for measuring risk behaviors in related research areas . Using theoretical interpretations proposed by Dir et al, conscientious was considered functionally equivalent to premeditation, neuroticism was represented by negative urgency, openness to experience was represented by positive urgency, and extraversion was represented by sensation seeking.…”
Section: Prevalence and Demographicsmentioning
confidence: 99%
“…On the other hand, the UPPS-P model, derived from the extant literature and updated over time, proposes five factors of impulsivity: (lack of) perseverance, (lack of) premeditation, positive and negative urgency, and sensation-seeking 31,32 . Empirical studies have repeatedly reported an association between GD and impulsive tendencies [33][34][35][36] . In particular, higher lack of perseverance, and positive and negative urgency levels have been found to be the features that best distinguish between patients with GD and HC 37,38 .…”
mentioning
confidence: 99%